Comparing radiographic changes associated with fixed retainer and bisphosphonate (zoledronic acid) injection for retention after fixed orthodontic treatment. - سنكري, يولاندا; حازم حسن (Latakia University Journal -Medical Sciences Series, 2024)
Relapse is considered one of the most common problems after completing orthodontic treatment for both the patient and the doctor, and it usually occurs in the lower jaw more than the upper jaw, especially in the anterior region. Therefore, research has recently increase aiming to find a technique that has less relapse, more effectiveness, and more accepted by the patient. Objective: Evaluation of radiographic changes associated with retention by bisphosphonate injection compared with cemented permanent lingual retainer. Materials and methods: The research sample consisted of 8 patients who had completed fixed orthodontic treatment. They were divided into two groups; each group consisted of 4 patients, the first group had a lingual fixed retainer, and the second group was injected with zoledronic acid for retention. Results: The results of the current study showed that there were no significant differences regarding the angle formed between the axis of the right and left lower incisors for both methods. Conclusion: There is no difference in the rate of relapse between retention using a fixed retainer and retention using bisphosphonate injection.